Implications of COVID-19 Pandemic on Probation Service Delivery in London, England - Haastrup, Adesanya Michael (Digital Repository of Theses - SSBM Geneva, 2025)
The COVID-19 pandemic has profoundly impacted probation services in London, England, necessitating a shift from traditional in-person supervision to remote and virtual methods. This study explores how these changes influenced the efficiency of probation service delivery, workload of probation officers, and quality of supervision provided to probationers during and after the pandemic. This research adopts a mixed-methods approach, utilising surveys and administrative data to capture insights from probation officers, probationers, and other stakeholders. Quantitative data, including compliance rates and appointment schedules, complement qualitative insights to understand the impact of the pandemic comprehensively. Initial findings indicate that remote supervision presented significant challenges. Probation officers faced increased workloads, adapting to new technologies while managing larger caseloads. These operational pressures exacerbated stress and reduced their ability to maintain depth of engagement, which is essential for adequate supervision. Moreover, virtual methods are often less effective than face-to-face interactions, particularly for high-risk offenders who require intensive intervention. This study underscores the limitations of remote supervision, highlighting its reduced capacity to foster meaningful relationships between officers and probationers, which are critical for rehabilitation and compliance. However, it also identifies logistical advantages, such as improved accessibility for some probationers, suggesting the potential benefits of a hybrid model combining in-person and virtual methods. These findings emphasise the need for a balanced approach that integrates technology without compromising the relational aspect of probation services. By addressing the identified challenges, this research provides actionable recommendations to improve the resilience and effectiveness of probation services in London, particularly in managing future crises. These insights will contribute to broader discussions on adapting public services to unforeseen disruptions, ensuring that they remain equitable, efficient, and impactful. Keywords: Probation services, Remote supervision, Service efficiency, Public service delivery, COVID-19 pandemic